1983
DOI: 10.1210/jcem-57-3-482
|View full text |Cite
|
Sign up to set email alerts
|

Renin Exists in Human Adrenal Tissue*

Abstract: Readily detectable levels of renin activity were demonstrated in human adrenal tissues. This activity was inhibited by specific antibody raised against pure renin, indicating that it was not due to the nonspecific action of proteases. The renin activity was predominantly in the cortex rather than in the medulla of the adrenal. An adrenal gland that was surgically removed from a patient with Cushing's disease and had high renin activity was used for further characterization of the enzyme. It shared many biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…Renin has been shown, immunohistochemically, to exist in human adrenal tissue, and biochemical characterization of this adrenal enzyme has demonstrated similarities between this renin and purified kidney renin [11]. The renin activity was predominantly in the cortex rather than in the medulla of the adrenal tissue.…”
Section: Discussionmentioning
confidence: 95%
“…Renin has been shown, immunohistochemically, to exist in human adrenal tissue, and biochemical characterization of this adrenal enzyme has demonstrated similarities between this renin and purified kidney renin [11]. The renin activity was predominantly in the cortex rather than in the medulla of the adrenal tissue.…”
Section: Discussionmentioning
confidence: 95%
“…Samples from differential and density gradient centrifugation were treated with 0.1 vol of phosphate buffer (0.2 M, pH 7.0) containing 1% Triton X-100 before assay. Specific immunoreactive renin activity was determined using antirenin antibody to distinguish it from nonspecific renin-like activity of proteases according to the method previously detected (4,5,15,16). 25 to 50 Ml of the samples were incubated with 10 ,ul ofdiluted (1:500) rabbit antiserum raised against pure rat kidney renin (17) at 4VC for 20 h. This antibody used resulted in 50% inhibition of renin activity (40.0 ng Ang I/h) in a rat kidney extract at a dilution of 1:10,000 and complete inhibition at a dilution of 1:1,000.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, renin plays a central role in blood pressure regulation. On the other hand, recent biochemical and immunological studies revealed that renin exists in the adrenal gland of various mammalian species (1)(2)(3)(4)(5). It was also demonstrated that this adrenal renin is primarily located in the zona glomerulosa cells rather than the fasciculata or medullary cells (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renin-like activity has been detected in the adrenal glands of rat (Ryan 1967, Ganten et al 1974, Naruse & Inagami 1982, Doi et al 1983, 1984a, Inagami et al 1984, Nakamaru et al 1985 and other species (Hayduk et al 1970, Ganten et al 1976, Naruse et al 1983, 1984, Racz et al 1992. Nephrectomy elicits a rapid and marked increase in the adrenal renin activity indicating that this enzyme is endogenous to the adrenal rather than due to contamination by plasma renin of renal origin (Naruse & Inagami 1982, Doi et al 1984a,b, Inagami et al 1984.…”
Section: Introductionmentioning
confidence: 98%